The Implementation of Problem-based Learning on Students’ Speaking Skills in English for Personality Development Course - Utami, Ketut Herya Darma; Rismadewi, Ni Wayan Monik (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
This research aimed to determine the effect of the implementation of Problem-based Learning on improving students' speaking skills in the English for Personality Development course. This research was qualitative research supported by quantitative data, involving 28 students of the Ganesha University of Education. The data were collected using pretest and posttest, questionnaires, semi-structured interviews, and observation sheets. This research used one group pre-test post-test, to determine the effect of PBL on students’ speaking skills. Meanwhile, qualitative data were obtained from observation sheets, questionnaires and semi-structured interviews with students regarding their perceptions of the PBL learning model. Based on the results obtained from statistical data, questionnaires, and observations, it can be concluded that the PBL model influences on improving students' English-speaking skills in the English for Personality Development course. The average score of the pretest and post-test shows a significant difference (Sig. <0.005). This is also supported by the result of the questionnaire and observation data where students responded positively to the PBL model in class in improving their speaking skills. This means that there is an influence of the PBL model in improving students’ English-speaking skills